MODERATISME ISLAM MELALUI KURIKULUM PENDIDIKAN PESANTREN (Studi Perbandingan Pada Implementasi Kurikulum Pendidikan Pondok Pesantren Fadlillah dan Pondok Pesantren Jawaahirul Hikmah dalam Membentuk Sikap Moderat Beragama Santri) - Rohman, Abid; Mansyur, Munir; Hajar, Imam Ibnu (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Islamic moderation through the educational curriculum at the Fadllillah and the Jawaahirul Hikmah Islamic Boarding School is a qualitative study with comparative analysis. The reason for choosing the Fadllillah Islamic Boarding School is because this institution has collaborated the Madrasah education curriculum with the local educational curriculum system of the Tarbiyatu al-Mu'allimin al-Islamiyyah and the Sufism teachings. Meanwhile, the selection of the Jawahirul Hikmah Islamic Boarding School cause this institution has implemented a formal school education system by collaborating the values ​​of Islamic boarding school character education and the Sufism teachings of the kiai who cares for this institution too like; daily dhikr, ma'rifat teachings. All data in this study was collected using observation, interviews, and documentation. The results of this study conclude that; The two institutions above have educated their students with a moderate attitude in religion through Islamic boarding school education curriculum by adapting to government regulations. The implications of this research confirm that; 1) an Understanding of Islamic moderation has been instilled since at Islamic boarding school; 2) the development of the Islamic education curriculum in Islamic boarding schools is always carried out flexibly, which is influenced by the leadership of kiai.